River pollution abatement: Decentralized solutions and smart contracts - Jens Gudmundsson; Jens Leth Hougaard (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2021)
In river systems, costly upstream pollution abatement creates downstream welfare gains. Absent adequate agreement on how to share the gains, upstream regions lack incentives to reduce pollution levels. We develop a model that makes explicit the impact of water quality on production benefits and suggest a solution for sharing the gains of optimal pollution abatement, namely the Shapley value of an underlying convex cooperative game. We provide a decentralized implementation through a smart contract to automate negotiations. It ensures a socially optimal agreement supported by fair compensations to regions that turn to cleaner production from those that pollute.
Keywords: C7; D47; D62; Q52; Q25; 330; River pollution; Decentralized mechanism; Shapley value; water quality; smart contracts